Multivatiable control of a distillation column - Kotyk, Josef; Macháček, Jiří (Univerzita Pardubice, 1995)
Two methods of automatic control of multivariable systems design are compared in this paper: Inverse Nyquist Array and decoupling method. Both methods reduce the non-diagonal elements of the system transfer functions matrix by means of suitable compensator. The multivariable control problem is in such way, simplified to single variable control loops. The results of the simulation and experiments on the real pilot plant distillation column are given.